Proposta conceital de desenvolvimento de desenvolvimento de turbina eólica para agricultura familiar com inovações tecnológicas para baixas velocidades de vento - Albiero, Daniel (2012)
The small farms are an important sector of Brazilian Agribusiness. They produce the most food in Brazil. However a challenge for these farmers from Ceará is to use wind energy, because the wind has low speed (winds <6 m.s-1) The subject this paper was to propose a wind power system for small farms of Ceará with technological innovations: new airfoil for wind power applications, counter rotative rotors, winglets, Toroidal Accelerator Rotor Platform (TARP), vegetal fibers materials and electric generation through three-phase inductor motor. Engineering tool and specific methodologies were used and a technical viable solution was showed. All systems were designed and sized and a wind turbine adequate for needs was proposed. By estimates this system provides electrical energy at low cost and through smart grids and distributed generation can to increase income of small farmers